2006
DOI: 10.1002/cncr.21663
|View full text |Cite
|
Sign up to set email alerts
|

Problems with the current diagnostic approach to complex atypical endometrial hyperplasia

Abstract: The gas–liquid volumetric mass transfer coefficient was determined by the dynamic oxygen absorption technique using a polarographic dissolved oxygen probe and the gas–liquid interfacial area was measured using dual‐tip conductivity probes in a bubble column slurry reactor at ambient temperature and normal pressure. The solid particles used were ultrafine hollow glass microspheres with a mean diameter of 8.624 µm. The effects of various axial locations (height–diameter ratio = 1–12), superficial gas velocity (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Therefore, previous estimates of carcinoma risk based on consensus diagnoses of SH, CH, and AH (Kurman et al, 1985;Ferenczy and Gelfand, 1989;Montgomery et al, 2004;Horn et al, 2007) may require revision. Our findings reaffirm the need to improve the sensitivity and specificity of AH diagnoses (Soslow, 2006) and efficiently identify the rare nonatypical EH lesions that are likely to progress. Modern outpatient biopsy techniques achieve over 90% sensitivity for detecting carcinoma (Dijkhuizen et al, 2000), but better endometrial assessment (Zaino, 2000), histopathologic classifications (Mutter, 2002), and candidate molecular markers (Mutter, 2000) deserve further study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, previous estimates of carcinoma risk based on consensus diagnoses of SH, CH, and AH (Kurman et al, 1985;Ferenczy and Gelfand, 1989;Montgomery et al, 2004;Horn et al, 2007) may require revision. Our findings reaffirm the need to improve the sensitivity and specificity of AH diagnoses (Soslow, 2006) and efficiently identify the rare nonatypical EH lesions that are likely to progress. Modern outpatient biopsy techniques achieve over 90% sensitivity for detecting carcinoma (Dijkhuizen et al, 2000), but better endometrial assessment (Zaino, 2000), histopathologic classifications (Mutter, 2002), and candidate molecular markers (Mutter, 2000) deserve further study.…”
Section: Discussionsupporting
confidence: 71%
“…Distinguishing low-risk EH lesions that can be conservatively managed with progestogen-based treatment plus surveillance from higher-risk EH lesions that require immediate surgical treatment has clinical implications (Clark et al, 2006;McCluggage, 2006;Soslow, 2006). There is no consensus on the management of SH or CH (Clark et al, 2006), which make up most EH diagnoses, but these lesions are thought to pose only modest risk of progression to carcinoma (Marsden and Hacker, 2001;Montgomery et al, 2004).…”
mentioning
confidence: 99%
“…Recent reports suggested that complex-atypia cells are found in the background of overt cancers [13][14][15]. This possibility was ruled out in the present study as all cases diagnosed initially as complex hyperplasia with atypia were re-evaluated and the histology was confirmed.…”
Section: Discussionmentioning
confidence: 75%
“…However, the simple hyperplasia without atypia is similar to the normal proliferative endometrium and the complex hyperplasia with nuclear atypia resembles the well differentiated endometrioid adenocarcinoma [9]. Therefore, many previous studies have exhibited that the coexisting rate of endometrial carcinoma in patients with AEH varies from 15% to 54% [7,10-13].…”
Section: Discussionmentioning
confidence: 99%